ESTIMATION OF SCATTERED NEUTRONS CONTRIBUTION IN A NEUTRON CALIBRATION BUNKER USING A MONTE CARLO SIMULATION. Issue 1 (17th January 2022) - Obeid, M H; Ismail, A; Bitar, A; Shweikani, R
Abstract: The contribution of scattered neutrons is inevitable in neutron calibration facilities. This contribution complicates the measurements of neutron radiation, therefore, it should be estimated to correct the response of neutron probe instruments. In the present work, Monte Carlo simulation was performed for a neutron calibration bunker using the MCNP-4C code. This simulation aimed to calculate the contribution ratio of scattered neutrons to the neutron field. To simulate the neutron field, 241 Am-Be neutron source defined in the ISO 8529-1 was used. The results of the simulation reported in this work were found to be consistent with those found experimentally in previous work. Additionally, the distribution of both the ambient dose equivalent rate and the contribution ratio of scattered neutrons in the bunker were mapped using this simulation.